EFISIENSI RENCANA PEMBANGUNAN FLY OVER PERSIMPANGAN JL. KOL. BURLIAN â JL. TANJUNG API API KOTA PALEMBANG UNTUK MENGATASI KEMACETAN - Kurnia, Aztri Yuli; Rhaptyalyani, Rhaptyalyani (CANTILEVER, 2016)
The existence of Jl. Kol. Burlian - Jl. Tanjung Api Api junction becomes very strategic because it becomes the entrance and exit of Palembang city. The intersection is access to several places such as Sultan Mahmud Badaruddin II Airport, Tanjung Api-Api Port, and the border road to Banyuasin. The position of Jl. Kol. Burlian - Jl. Tanjung Api Api junction which is very strategic cause the long queue of vehicles causing traffic jam. To overcome this the South Sumatra Provincial Government will build a fly over at Jl. Kol. Burlian - Jl. Tanjung Api Api junction. Basically the construction of this fly over as an effort to reduce the volume density of vehicles that accumulate at Jl. Kol. Burlian - Jl. Tanjung Api Api junction. The result of calculation using MKJI method calculation, the delay value before the existing fly over or signal condition is 46 seconds / smp, while the length of delay after the fly over dropped dramatically to 16 seconds / smp. Likewise with the calculation using the VISSIMprogram, the results obtained are not much different from the MKJI method, which is 45.23 seconds / smp for the condition before the fly over, and 15.18 seconds / smp for the condition after the fly over. Thus, the development of an efficient fly over in reducing the length of vehicle delays at Jl. Kol. Burlian - Jl. Tanjung Api Api junction, so it is expected to overcome the congestion that always occurs at the intersection.